Edukasi dan Pemeriksaan Glukosa Darah Sewaktu (GDS) Sebagai Upaya Deteksi Dini Diabetes pada Lansia di Distrik Demta Kabupaten Jayapura - Fajar Bakti Kurniawan; Dyan Puji Lestari; Roganda Simanjuntak (Indonesian Journal Publisher, 2025)
Globally, the number of individuals with diabetes aged 20–79 is approximately 540 million and is expected to continue rising. The majority of diabetes cases, around 90%, are diagnosed as type 2 diabetes mellitus (T2DM). The impact of diabetes is associated with several chronic complications. These complications contribute to a decline in quality of life and may lead to a loss of independence, particularly among elderly patients. One approach to addressing diabetes-related health issues in elderly patients is through preventive and promotive efforts. One such effort is health screening for elderly individuals, aimed at early disease detection or preventing the onset of diabetes. Regular blood glucose testing is recommended, especially for individuals whose glucose levels exceed the normal threshold, to ensure timely treatment and prevention. In addition to routine blood glucose monitoring, increasing public awareness and knowledge about diabetes mellitus is essential to facilitate early prevention efforts. As a result of this initiative, several respondents with diabetes were identified, and there was an increase in knowledge regarding diabetes and its prevention.